2020
DOI: 10.1002/rev3.3196
|View full text |Cite
|
Sign up to set email alerts
|

Variables Related to Academic Help‐Seeking Behaviour in Higher Education – Findings from a Multidisciplinary Perspective

Abstract: Universities admit increasingly diverse student cohorts with varying academic entry standards. To address students' varying academic prerequisites, academic support servicessuch as literacy and numeracy supportare offered to ensure student success. However, students often do not engage. Aimed at mapping variables related to a student's decision to seek academic help in order to identify gaps, this systematic scoping review informs future research and supports the provision of academic support services for dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 144 publications
3
19
0
2
Order By: Relevance
“…Specifically, girls presented higher scores in the perceived emotional cost of help seeking and avoidance of help seeking, which is consistent with previous studies that show that girls are more likely to have negative attitudes towards seeking help [13,14]. However, these differences are not entirely clear because some studies have found contradictory results [12]. These discrepancies may be due to the influence of sociocultural variables on gender.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, girls presented higher scores in the perceived emotional cost of help seeking and avoidance of help seeking, which is consistent with previous studies that show that girls are more likely to have negative attitudes towards seeking help [13,14]. However, these differences are not entirely clear because some studies have found contradictory results [12]. These discrepancies may be due to the influence of sociocultural variables on gender.…”
Section: Discussionsupporting
confidence: 89%
“…In these cases, AHS can be considered a threat to socio-emotional aspects [3,10,11]. Academic help-seeking behavior has been related to sociodemographic variables such as gender, although results are by no means conclusive [12]. Some studies report that men are more likely to seek help than women (Amarasuriya et al [13] and Roessger et al [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, a lo largo de estos años, la investigación indica que la comprensión del fenómeno de búsqueda de ayuda posee diversas dimensiones y complejidades (Karabenick y Dembo, 2011). Para una visión general y detallada, ver Bornschlegl et al (2020), Chowdhury and Halder (2019), Karabenick and Berger (2013).…”
Section: Búsqueda De Apoyo Académicounclassified
“…La búsqueda de ayuda académica representa una estrategia general de aprendizaje y resolución de problemas, vinculada a las habilidades de aprendizaje autorregulado de los estudiantes (Bornschlegl et al, 2020;Karabenick, 2014;Karabenick & Gonida, 2018;Reeves, 2014;Karabenick & Newman, 2011). Pedir ayuda permite a los alumnos enfrentar dificultades académicas obteniendo la asistencia de otros (Ames & Lau, 1982;Nelson-Le Gall, 1981).…”
Section: Búsqueda De Ayuda Académicaunclassified